The use of traditional herbal medicines among palliative care patients at Mulanje Mission Hospital, Malawi - Chisaka, Joseph Wangisani (Department of Public Health and Family Medicine, 2020)
Background: The prevalence of use of traditional medicines by patients receiving palliative care is poorly documented. In 2002, the World Health Organisation estimated about 4 billion people (80% of the world’s population) used traditional medicines for some aspect of primary healthcare, with 90% of users living in low and middle income countries. Studies in Africa have shown that patients on palliative care are more likely to use traditional medicines especially after the diagnosis of cancer. This study describes the prevalence of and reasons for TM use amongst PC patients and also explores the common herbs used by this population. Methodology: A mixed method descriptive cross sectional study design was used including the following: questionnaire administered to patients attending palliative care clinic and focus group discussions with palliative care patients. Results: 60.4% of palliative care patients (n = 96; males = 53%) reported use of traditional herbal medicines. The majority of survey participants had the diagnosis of cancer (94%; n = 90) and HIV (89%; n = 85). Traditional herbal medicine use was common in participants who had the following symptoms: diarrhoea 83%, anorexia 63%, pain 61% etc. Traditional medicine use was not associated with age, gender, education, occupation, distance from hospital, diagnosis or symptom. 62% of the participants who used herbal medicines did not know the herbs they were taking. Kigelia Africana, Moringa oleifera, Cyphostema sp, and Strychnos innocua were the common herbs used. Cultural practices, limitations of conventional health system and credibility of traditional healers were the main reasons for using traditional herbal medicines. Conclusion: Use of traditional herbal medicines is high among patients receiving palliative care at Mulanje Mission hospital mainly for symptom management and cancer. Further research is needed to investigate effectiveness of identified herbs and also assess their potential herb-drug interactions. Ongoing work including liaison with traditional healers would assist to formulate effective local palliative care management programs that are sensitive to traditional medicine practices.